Impact of Corporate Social Responsibility on Job Attitudes: Job Satisfaction and Organizational Commitment of Banking Sector Employees of Pakistan - Mavra Khan; Sadia Sarwar; Hiba Khan (SEISENSE (PRIVATE) LIMITED, 2018)
The study is conducted to highlight the employees’ perspective of CSR in the banking sector of Pakistan and its impact on their job attitudes: job satisfaction and organizational commitment. Primary data were collected from 177 employees working in 22 different banks of Lahore (Pakistan). Stratified random sampling technique was used for sample selection. The population included all the banks in Lahore. Results show the existence of a direct relationship between a) CSR and Organizational Commitment b) CSR and Job Satisfaction.